Stability of a Class of Fractional-Order Nonlinear Systems - Tianzeng Li; Yu Wang (Discrete Dynamics in Nature and Society)
In this letter stability analysis of fractional order nonlinear systems is studied. Some new sufficient conditions on the local (globally) asymptotic stability for a class of fractional order nonlinear systems with order 0<α<2 are proposed by using properties of Mittag-Leffler function and the Gronwall inequality. And the corresponding stabilization criteria are also given. The numerical simulations of two systems with order 0<α<1 and two systems with order 1<α<2 illustrate the effectiveness and universality of the proposed approach.